Exploring substrate promiscuity of chlorophenol hydroxylase against biphenyl derivatives. Issue 105 (13th October 2015) - Ren, Hejun; Li, Qingchao; Fang, Xuexun; Yu, Dahai
Abstract : The substrate promiscuity of 2, 4-dichlorophenol hydroxylase against biphenyl derivatives was explored. This enzyme may be used as a potentially useful catalyst in the bioremediation of aromatic contaminants. Abstract : A 2, 4-dichlorophenol hydroxylase, whose gene was derived from the metagenomic library of polychlorinated biphenyl (PCB)-contaminated soil has been found to exhibit a broad range of activity for single ring aromatic contaminants including chlorophenols (CPs) and their homologues. In this study, we intended to explore its activity to aromatic bicyclic compounds such as biphenyl and its derivatives which are also important persistent environmental contaminants. Results demonstrated that the enzyme exhibited broad substrate specificity to selected biphenyl derivatives including hydroxylated biphenyls, halogenated biphenyls, PCBs and hydroxylated PCBs, which extended its substrate promiscuity apart from CPs and their homologues. The enzymatic activities against these aromatic bicyclic compounds were congener dependent and the position and type of the substituent on biphenyl derivatives greatly affected the substrate priority of this enzyme. The hypothesis of the catalysis preference of the enzyme on the aromatic ring was preliminarily proposed on the basis of the analyses of the enzymatic activities against biphenyl derivatives. The high activity and removal ability of this enzyme against selected aromatic contaminants would make it a very promising catalyst for bioremediation of biphenyl derivatives.